The Effect of Clinical Pharmacy Services on Patient Safety in Saudi Arabia’s Hospitals: A Systematic Review - Ahmad Alzahrani; Ahmad Almohammadi; Khalid Alkhormani; Abdullah Alotaibi; Adel Almalki; Hassan Alzahrani; Jawad Hamad Aljohani (International Journal of Medical Toxicology and Legal Medicine, 2024)
This paper aims at demonstrating how Clinical Pharmacy services (CPS) contribute to improving patient safety throughout the world. This resulted because in Saudi Arabia, the assessment of such a prominent impact of technology requires a well-structured methodological approach.To measure the ability of CPS in enhancing patient safety in Saudi Arabian hospitals.The materials from 2020 to 2024 have been analyzed by the data of PubMed and Scopus. Specific inclusion criteria were directed to CPS interventions that address patient safety.CPS improved medication reconciliation, reduced adverse drug reactions (40%), and minimized medication errors (up to 35%).The multifaceted nature of CPS in Saudi healthcare makes CPS improve the safety of patients in the kingdom’s healthcare settings but obstacles such as workforce paucity and policy deficiencies hamper the expansion of CPS.